Learning English through Scaffolded Assistance in Iraqi EFL Classroom (Journal of the College of Languages (JCL), 2014)
Learning a foreign language is a highly interactive process, and a belief that communicative activities foster a great amount of linguistic production provides language practice and opportunities for negotiation of meaning during communicative exchanges. Thus, this study examines what benefits learner-centered classroom setting offers compared with that of teacher–centered classroom, and how less proficient learners accomplish their tasks and activities with scaffolded help during interaction with the help of proficient classmates and under the guidance of a skilful person, i.e., the teacher. The subjects participating in this study are 30 Iraqi 4th year college students in the Department of English, College of Arts , University of Baghdad for the academic year 2012-2013. The students were working with groups of two or three. Their task was to make up different conversations and after each conversation, the teacher asked some questions to the group. Five teacher-student interactions were analysed. The results showed that learner-centeredness was beneficial for language learning in the following respects: 1-it triggered more scaffolding offered by the teacher and 2-interaction between learners actively occurred in learner – centered lessons. In addition when the teacher engaged in interaction with the students, he basically used repetition, paraphrases and nonverbal devices such as varying the pace of his/her utterances, facial expressions and pauses as scaffolding.